Enhanced Emitting Dipole Orientation Based on Asymmetric Iridium(III) Complexes for Efficient Saturated‐Blue Phosphorescent OLEDs - Kefei Shi; Chengcheng Wu; He Zhang; Kai‐Ning Tong; Wei He; Wansi Li; Zhaoyun Jin; Sinyeong Jung; Siqi Li; Xin Wang; Shaolong Gong; Yuewei Zhang; et al. (Advanced Science)
Abstract Three novel asymmetric Ir(III) complexes have been rationally designed to optimize their emitting dipole orientations (EDO) and enhance light outcoupling in blue phosphorescent organic light‐emitting diodes (OLEDs), thereby boosting their external quantum efficiency (EQE). Bulky electron‐donating groups (EDGs), namely: carbazole (Cz), di‐tert‐butyl carbazole (tBuCz), and phenoxazine (Pxz) are incorporated into the tridentate dicarbene pincer chelate to induce high degree of packing anisotropy, simultaneously enhancing their photophysical properties. Angle‐dependent photoluminescence (ADPL) measurements indicate increased horizontal transition dipole ratios of 0.89 and 0.90 for the Ir(III) complexes Cz‐dfppy‐CN and tBuCz‐dfppy‐CN, respectively. Analysis of the single crystal structure and density functional theory (DFT) calculation results revealed an inherent correlation between molecular aspect ratio and EDO. Utilizing the newly obtained emitters, the blue OLED devices demonstrated exceptional performance, achieving a maximum EQE of 30.7% at a Commission International de l'Eclairage (CIE) coordinate of (0.140, 0.148). Optical transfer matrix‐based simulations confirmed a maximum outcoupling efficiency of 35% due to improved EDO. Finally, the tandem OLED and hyper‐OLED devices exhibited a maximum EQE of 44.2% and 31.6%, respectively, together with good device stability. This rational molecular design provides straightforward guidelines to reach highly efficient and stable saturated blue emission.